2022
DOI: 10.3389/fpsyg.2022.946142
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of oral narrative textual competence and spelling skills to written narrative textual competence in bilingual language-minority children and monolingual peers

Abstract: This study investigates the developmental pattern and relationships between oral narrative textual skills, spelling, and written narrative textual skills in monolingual and bilingual language-minority (BLM) children, L1-Chinese and L2-Italian. The aims were to investigate in monolingual and BLM children: (1) the developmental patterns of oral and writing skills across primary school years; (2) the pattern of relationships (direct and mediated) between oral narrative textual competence, spelling skills, and wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The results of BLMs’ poor performances that emerged in lexical, reading and spelling skills are partially in accordance with the literature. Specifically, our results aligned with previous studies investigating bilingual language-minority children with L1-Chinese and L2-Italian whose results demonstrated difficulties in literacy skills during different periods of development (for example, Bonifacci and Tobia, 2016 ; Vettori et al 2022a ). While there may be several explanations, we speculate that these results are attributed, at least partially, to the fact that BLM children grow up with less L1-Italian language input and opportunities to practice the L1-Italian language beyond school.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of BLMs’ poor performances that emerged in lexical, reading and spelling skills are partially in accordance with the literature. Specifically, our results aligned with previous studies investigating bilingual language-minority children with L1-Chinese and L2-Italian whose results demonstrated difficulties in literacy skills during different periods of development (for example, Bonifacci and Tobia, 2016 ; Vettori et al 2022a ). While there may be several explanations, we speculate that these results are attributed, at least partially, to the fact that BLM children grow up with less L1-Italian language input and opportunities to practice the L1-Italian language beyond school.…”
Section: Discussionsupporting
confidence: 90%
“…Some recent studies conducted in Italian primary schools have shown that bilingual language minority children underperform in emergent literacy skills such as notational awareness ( Incognito et al, 2021 ); spelling ( Bonifacci et al, 2020 , 2022 ; Vettori et al, 2022a , b ) and lexical skills compared to monolingual peers. The population of bilingual language minority children represent a very specific type of bilingualism and refer to those children who are exposed to the acquisition of the second language in an intensive and regular way only when they start formal instruction at school, while they continue to use their first language to communicate and interact at home ( Hoff et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation